Mitogen activation induces the enhanced synthesis of two heat-shock proteins in human lymphocytes (The Rockefeller University Press, 1988)
We have used mitogenic lectin (PHA) and a monoclonal antibody (OKT3) to stimulate human peripheral blood (G0) lymphocytes, in the presence of monocytes, and have found two major preferentially synthesized proteins, 73 and 95 kD, which are induced by the mitogens. The elevated synthesis of both proteins begins approximately 4-6 h after mitogen addition (early to mid G0/G1) before entry into first S phase. Maximum synthesis of both proteins is reached by 12 h after mitogen addition when P95 synthesis represents approximately 4%, and P73 approximately 2%, of the total protein synthesis, compared with less than 0.5% for each protein in cells cultured without mitogen. Thus, the proteins appear to be major components of activated cells. We find that both P73 and P95 are induced by heat stress as well as mitogenic stimulation. The induction of the proteins is not affected by either deleting glucose from the culture media or, alternatively, by supplementing it. Using polyclonal antibodies prepared to each of the proteins isolated from mitogen activated cells and monoclonal antibodies that were raised to heat shock proteins, we are able to show that P95 is electrophoretically and immunologically identical to the HSP 90 induced by heat stress. P73 is one of the 70 kD HSPs, (termed HSC 70; Pelham, H. R. B. 1986. Cell. 46: 959-961), but is different from the most strongly heat inducible form of HSP 70 (72 kD). The distribution of both proteins in subcellular fractions of mitogen activated lymphocytes is similar to the reported localization of the respective HSP's in other cell types. The results suggest that HSP 90 and HSC 70 may have functional roles in stress response and growth processes of human lymphocytes.